RANCANG BANGUN DATA LOGGER MONITORING VIBRASI PADA MOTOR LISTRIK 6,3 KV BERBASIS IOT SECARA REAL TIME DI PLTU JERANJANG - Putu Agus Satriya Guna Adnyana; Rukmi Sari Hartati; I Gede Dyana Arjana (Jurnal SPEKTRUM, 2022)
As a power plant industry, PLTU Jeranjang OMU (Operation and Maintenance Unit) owned oneof 6.3 kV nominal voltage induction motor that has critical characteristic that drives the waterpump into the boiler room which always has to operate. This motor has been equipped withtemperature sensor in real time that can monitor the temperature of bearing motor. However,manual control is still applied in vibration monitoring. It is done by taking the vibration data oncea week, and there is no deviation data found in real time. The result of this study shows that theprototype of IoT-based vibration monitoring data logger that is designed using the blynkapplication obtained the average of sensor deviation of 2%. Alarm notification of each sensorsdeliver "warning" if the vibration value indicates ? 4,5-70 mm/s and alarm notification delivers"emergency" if the vibration value indicates ? 7,1 mm/s in concordance with the ISO 10816-3vibration standard. Although, the performance of sensor data storage has successfully storingthe data with 8 GB microSD card, then will be fully charged in 4629 days or 154 months and 3days.